## Discussion Forum

Que. | Let a(x, y), b(x, y,) and c(x, y) be three statements with variables x and y chosen from some universe. Consider the following statement:
(∃x)(∀y)[(a(x, y) ∧ b(x, y)) ∧ ¬c(x, y)] Which one of the following is its equivalent? |

a. | (∀x)(∃y)[(a(x, y) ∨ b(x, y)) → c(x, y)] |

b. | (∃x)(∀y)[(a(x, y) ∨ b(x, y)) ∧¬ c(x, y)] |

c. | ¬ (∀x)(∃y)[(a(x, y) ∧ b(x, y)) → c(x, y)] |

d. | ¬ (∀x)(∃y)[(a(x, y) ∨ b(x, y)) → c(x, y)] |

Answer:¬ (∀x)(∃y)[(a(x, y) ∧ b(x, y)) → c(x, y)] |